Isotope analysis reveals the relevance of local wild plants in diet and maize as an exotic commodity in pre-Hispanic Patagonia - Alejandro Serna; Luciano Prates; Lucio González Venanzi; Daniela Saghessi; Emiliano Mange; Victoria Romano; Javier A. Montalvo-Cabrera; Domingo C. Salazar-García (Scientific Reports)
Abstract The acknowledgment of plants as significant components in hunter-gatherer diets has provided new insights into past interactions between these groups and their environments, as well as between groups with different economies and social structures. The Patagonia region, South American Southern Cone, has been traditionally perceived as dominated by game hunting. This perception has changed by recognizing a broader spectrum of diet, where local wild and exotic domesticated plants, would have been intertwined in these hunter-gatherer lives. However, the nature of the archaeological record preservation obscures an accurate assessment of their role. Here, we quantified the contribution of plants and other resources to hunter-gatherer paleodiets through biomolecular methods and statistical analysis (multivariate and Bayesian). We analyzed the carbon and nitrogen stable isotope composition (δ13Ccol, δ15N) of human remains (n = 30) and fauna/flora (n = 52) from Northern Patagonia, and radiocarbon dated specific individuals related to exotic domesticated plants (maize). Our results show that one-third of the overall intake was based on the systematic exploitation of local wild plants, while maize appears to have functioned as an imported edible commodity obtained from distant food producers.